Measuring the Degree of Internationalization of a Firm - Sullivan, Daniel (Journal of International Business Studies, 1994)
In spite of both positivistic and instrumental research, the reliability of measuring the degree of internationalization of a firm remains speculative. We collected data on nine attributes of seventy-four American manufacturing MNCs. Alpha, factor, and frequency analyses revealed a linear combination of five variables with a reliability coefficient of .79 as a measure of the degree of internationalization of a firm. We discuss the statistical and conceptual properties of the scale and their implications for content and construct validity.